PENGARUH PENDIDIKAN PESANTREN TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMAI AL-MA`ARIF SINGOSARI MALANG - Abd Razaq An-nafa`i; Nur Hasan; Khoirul Asfiyak (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The purpose of this study was to determine the effect of pesantren education on student achievement in PAI subjects at Singosari Malang Public High School. The instruments used in this study were questionnaires and interviews. while for data collection using observations, documents, questionnaires and interviews. The sample consisted of all class X IIS consisting of 35 students who live in boarding schools. After collecting data, the researcher analyzes the data by scoring, so that each question is given a score to find out the percentage of the answer. Then the researchers conducted several tests consisting of validity tests, validity testing was used to measure the questionnaire. Then the reliability test is used to determine whether the questionnaire is reliable and reliable. The reliability test in this study used the alpha crombach formula and obtained a value of 0.770. Whereas for simple linear regression analysis obtained based on the significant value of the coefficient table and obtained a significant value of 0,000> 0.05 so that it can be concluded that the variable X affects the Y variable.